Recovery of Hibernating Myocardium: What Is the Role of Surgical Revascularization?. Issue 2 (3rd December 2014) - Holley, Christopher T.; Long, Eric K.; Lindsey, Megan E.; McFalls, Edward O.; Kelly, Rosemary F.
Abstract Myocardial responses to chronic ischemia represent a continuum of adaptations resulting, over time, in a stress‐resistant phenotype. One such adaptation, hibernating myocardium (HM), has increased antioxidant capacity that protects against ischemia‐induced oxidative stress. Studies have suggested that revascularization alone may not fully restore cardiac function, highlighting the need for targeted therapies to serve as adjuncts to the innate healing process following revascularization. In our review, we discuss current understanding of HM and the recovery process following surgical revascularization, focusing on animal models of HM to understand implications for human patients. doi: 10.1111/jocs.12477 (J Card Surg 2015;30:224–231)